2008
DOI: 10.1007/s00248-008-9411-x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Aerobic Methanotrophic Bacteria in a Permafrost Active Layer Soil of the Lena Delta, Siberia

Abstract: With this study, we present first data on the diversity of aerobic methanotrophic bacteria (MOB) in an Arctic permafrost active layer soil of the Lena Delta, Siberia. Applying denaturing gradient gel electrophoresis and cloning of 16S ribosomal ribonucleic acid (rRNA) and pmoA gene fragments of active layer samples, we found a general restriction of the methanotrophic diversity to sequences closely related to the genera Methylobacter and Methylosarcina, both type I MOB. In contrast, we revealed a distinct spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
75
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(89 citation statements)
references
References 57 publications
8
75
3
Order By: Relevance
“…Another study on Siberia showed the same results to our study that type II methanotrophs were not detected, and similarly, only two genera, Methylobacter and Methylosarcina were presented in the study. And within these two genera, Methylobacter was dominated (Liebner et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study on Siberia showed the same results to our study that type II methanotrophs were not detected, and similarly, only two genera, Methylobacter and Methylosarcina were presented in the study. And within these two genera, Methylobacter was dominated (Liebner et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The reason to the unsuccessfully amplification of type II could be due to the bias of PCR. In the procedure of PCR, type II was artificially biased owning to the low abundance in our samples (Liebner et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Chelatococcus, classified as an aerobic methanogenic bacterium, belongs to an alphaproteobacterial family that can grow on a wide range of substrates (Liebner et al 2009). This organism may be a promising source of IL tolerant cellulases due to high microbial activity detected while in the presence of tetra butyl IL.…”
Section: Discussionmentioning
confidence: 99%
“…In the same area, specific clusters of methane oxidizing Proteobacteria closely related to Methylobacter psychrophilus and to Methylobacter tundripaludum were detected indicating a micro-diverse community on the species level (Liebner et al 2008). Also, highly divergent functional gene sequences of these methanotrophs were found in soils of the high Canadian Arctic (Pacheco-Oliver et al 2002).…”
Section: Methane Oxidizing Proteobacteriamentioning
confidence: 95%
“…In contrast, the population structure of methanogenic archaea in a permafrost affected peat in Siberia remained constant over a wide temperature range (Metje and Frenzel 2007). Also, a psychrophilic and little diverse methanotrophic community as detected near the permafrost table of Siberian polygonal tundra soils (Liebner and Wagner 2007;Liebner et al 2008) will likely require more time for resilience than the diverse mesophilic-psychrotolerant methanogenic community detected in permafrost soils of the same region (Ganzert et al 2006).…”
Section: Methane-cycling Communities Under Global Climate Changementioning
confidence: 99%